Monitoring building structures - Moore, J. F. A. (New York : Van Nostrand Reinhold, 1992)
There is an increasing number of buildings that require informed decisions to be made about their continued safety and serviceability. Although social and economic issues are often all-important influences, the technical issues nevertheless need to be addressed objectively, efficiently and reliably. The aim of this book is to bring together those techniques which can be used effectively to monitor building structures.